A systematic literature review of mathematics learning media and its contributions - Umi Hanifah; Dyah Worowirastri Ekowati; Dian Fitri Nur Aini (Universitas Muhammadiyah Malang, 2024)
A systematic literature review (SLR) aimed to define the trends and advances in mathematical semiotic reasoning research that have been published in journals with a scopus index, as well as their possibilities. Upon selecting the keyword